2015
DOI: 10.1002/pbc.25457
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and toxicities associated to chemotherapy in children with acute lymphoblastic leukemia and Gilbert syndrome. Usefulness of UGT1A1 mutational screening

Abstract: Differences in outcome were not found in patients with GS. Universal screening for GS appears to be not necessary in pediatric patients with ALL. However, when hyperbilirubinemia is observed, it must be rule out in order to avoid unnecessary changes in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…Therefore, therapy should not be cancelled or suspended, and an appropriate therapy schedule can be maintained. Recently, Berrueco et al (27) revealed that pediatric acute lymphoblastic leukemia (ALL) patients homozygous for the UGT1A1*28 allele tended to develop transient hyperbilirubinemia during cancer chemotherapy. They concluded that Gilbert syndrome should be taken into account when bilirubin levels increase without signs of hepatitis or hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, therapy should not be cancelled or suspended, and an appropriate therapy schedule can be maintained. Recently, Berrueco et al (27) revealed that pediatric acute lymphoblastic leukemia (ALL) patients homozygous for the UGT1A1*28 allele tended to develop transient hyperbilirubinemia during cancer chemotherapy. They concluded that Gilbert syndrome should be taken into account when bilirubin levels increase without signs of hepatitis or hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of GS on the course of cancers [3] and hematological malignancies in particular remains uncertain. The higher incidence of GS has been reported in childhood acute leukemia (14–20%) [5] , [6] , 7 , but no differences in outcome were found in patients with GS [7] . GS has also been associated with excessive toxicity of anticancer drugs in childhood acute lymphoblastic leukemia [8] , but improved outcomes in adult patients with Hodgkin lymphoma [9] .…”
mentioning
confidence: 72%
“…In a retrospective 159‐patient study, 23 pediatric patients with ALL had a homozygous TA 7 genotype and were treated with regimens containing methotrexate . Maximum bilirubin levels were significantly higher at baseline, 12.1 µmol/L ± 6.3 versus 6.8 µmol/L ± 3.3, p<0.0001 (0.7 mg/dL ± 0.36 vs 0.4 mg/dL ± 0.2), and with each treatment phase of induction, consolidation, intensification, and continuation in the patients with GS (Table ).…”
Section: Agents That May Inhibit Glucuronidationmentioning
confidence: 99%